Cerebral infarction by paradoxical gas embolism detected after laparoscopic partial hepatectomy with an insufflation management system: a case report - Kenji Shimizu; Masahiro Usuda; Yuta Kakizaki; Tomohiro Narita; On Suzuki; Kengo Fukuoka (Surgical Case Reports, 2023)
Abstract Background Laparoscopic surgery has reduced surgical morbidity and postoperative duration of hospital stay. Gas embolism is commonly known as a risk factor for all laparoscopic procedures. We report a case of severe cerebral infarction presumably caused by paradoxical CO2 embolism in laparoscopic partial hepatectomy with an insufflation management system. Case presentation A male in his 60 s was diagnosed with recurrence of liver metastasis in the right hepatic lobe after laparoscopic lower anterior resection for rectal cancer. We performed laparoscopic partial hepatectomy with an AirSeal® under 10 mmHg of intra-abdominal pressure. During the surgery, the patient’s end-tidal CO2 and percutaneous oxygen saturation dropped from approximately 40–20 mmHg and 100–90%, respectively, while the heart rate increased from 60 to 120 beats/min; his blood pressure remained stable. Postoperatively, the patient developed right hemiplegia and aphasia. Brain magnetic resonance imaging showed cerebral infarction in the broad area of the left cerebral cortex. Thereafter, transesophageal echocardiography revealed a patent foramen ovale, suggesting cerebral infarction due to paradoxical gas embolism. Conclusions A patent foramen ovale is found in approximately 15–20% of healthy individuals. While gas embolism is a rare complication of laparoscopic surgery, cerebral infarction must be considered a possible complication even if the intra-abdominal pressure is constant under 10 mmHg with an insufflation management system.